Design and testing of a novel building integrated cross axis wind turbine / Gwani Mohammed - Gwani , Mohammed (2018)
This thesis presents a novel design of a building integrated cross axis wind turbine (CAWT) that can operate under dual wind directions i.e. the horizontal wind from side and the vertical wind from the bottom of the turbine. The CAWT consisting of six horizontal blades and three vertical blades connected via connectors forms the cross axis configuration. An experiment was designed to test the performance of the CAWT on two different rooftops, i.e. on the gable and the vaulted shapes of a reduced-scaled building model. For benchmarking, the performance of a conventional straight bladed vertical axis wind turbine (VAWT) is tested under the same experimental conditions. The height of the CAWT and the VAWT above the rooftops were varied from Y = 100 to 250 mm. The effect of the roof shapes on the performance of CAWT was investigated. Comparisons were made between the performances of CAWT on the gable and vaulted rooftops. The CAWT was tested with different pitch angles, β = 0o, 5o, 10o, and 15o for the horizontal blades of the CAWT. The results obtained from the experimental study showed that at Y = 100 mm height above the gable and the vaulted rooftop, the maximum coefficient of power, Cp,max of the building integrated CAWT increased significantly by 266% at tip speed ratio, TSR (λ) of 1.1 and 246% at λ of 1.03, respectively, compared to the straight bladed VAWT. Further increase in CAWT height, Y above the gable rooftop showed that the CAWT outperformed the straight-bladed VAWT by 196%, 136% and 71 % at TSR of 1.16, 1.08, and 1.12 for Y = 150 to 250 mm respectively. Similar improvement in the performance of CAWT is also observed for all conditions of height above the vaulted rooftop. Furthermore, integrating CAWT on a building with gable or vaulted rooftop could yield 121% or 37% more energy than a bare-CAWT. In addition, CAWT mounted on the gable rooftop produces 66% more energy compared to the vaulted one under the same experimental conditions. Furthermore, 10o is the optimum pitch angle of the horizontal blade of the CAWT. Computational fluid dynamics (CFD) simulation results obtained from the flow field analysis indicated that the wind flow characteristics are strongly dependent on the profile of the roofs. Wind flowing above the vaulted rooftop has higher velocity, lower turbulence and lower pressure difference than the ones flowing above the gable rooftop. The double multiple streamtube (DMST) and blade element momentum (BEM) analysis produced similar pattern of graphs to the experimental results which indicates an agreement between the two analyses. Finally, an adaptive neuro-fuzzy inference system (ANFIS) methodology was used to predict the performance of power augmented VAWT. By using the root mean square error (RMSE), and the coefficient of determinant (R2), the accuracy of the ANFIS techniques was evaluated against the experimental results. The results showed that the developed ANFIS model is very effective and reliable in predicting the performance of power augmented VAWT.